2021
DOI: 10.1177/1049731521996457
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Considerations for Social Work Research With Vulnerable Children and Their Families

Abstract: The aim of this article is to impose solutions to the ethical dilemmas that derive from social work research involving vulnerable children. The main concern is how to balance the protection of children while progressing their participation. Several substitute mechanisms were put in place for protecting underage children. In particular, children were informed explicitly that participation was voluntary, they could pull out without risk of sanction, and their anonymity and confidentiality was guaranteed. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…They convey the perspectives of research participants in an honest, transparent, and accurate manner (NASW, 2021, 5.02[o]; Schroeder et al, 2019). They do not minimize or exaggerate problems to make political points or raise money (Sadzaglishvili et al, 2021). When using research to give voice to particular individuals or groups, SWRs ensure that they have informed consent to do so (Sobočan et al, 2019).…”
Section: Proposed Practice Standardsmentioning
confidence: 99%
“…They convey the perspectives of research participants in an honest, transparent, and accurate manner (NASW, 2021, 5.02[o]; Schroeder et al, 2019). They do not minimize or exaggerate problems to make political points or raise money (Sadzaglishvili et al, 2021). When using research to give voice to particular individuals or groups, SWRs ensure that they have informed consent to do so (Sobočan et al, 2019).…”
Section: Proposed Practice Standardsmentioning
confidence: 99%
“…Numerous studies in low-, middle-, and high-income countries have found that YWLS are vulnerable to negative health and social outcomes, including violence and victimization [5], economic and sexual exploitation [6], poor mental health [7], substance abuse [8], and sexually transmitted infections, including HIV/AIDS [9]. In the Republic of Georgia, YWLS are a relatively new phenomenon [10], with studies estimating that more than 1,600 youth work and/or live on the streets [11]. Although some research has examined the social, health, and economic needs of YWLS in Georgia [4], few studies have explored how social service providers perceive, manage, and respond to the stigma directed towards youth who live and/or work on the street.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, internal armed conflicts and the war with Russia forced the migration of families from Georgia's conflict zones in Abkhazia and South Ossetia to urban centers; once displaced, many families were forced to live in deteriorated conditions, which increased family stress and resulted in a number of children living and working on the streets [11]. In Georgia, YWLS represent multiple ethnic and linguistic groups, including ethnic Georgians, Azerbaijani Kurds, two Romani groups that speak distinct languages, refugees and internally displaced persons from Armenia, South Ossetia and Abkhazia, and youth from European and neighboring countries, e.g., Greece, Ukraine [4,10]. Since 2007, there has been a notable increase in the numbers of YWLS and families from Azerbaijan, identified as Azerbaijani or Azeri Kurds, who lack documentation and the ability to access many health and social services [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of street children is a social problem that often occurs in big cities in Indonesia (Darma et al, 2021). The economic crisis and urbanization situation has created various social problems, one of which is the phenomenon of street children which continues to increase (Sadzaglishvili et al, 2021). Being a street child is not a life choice expected by everyone, especially a small child, who should spend his childhood playing with his peers (Gowreesunkar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%